The diagnostic dilemma of cerebellopontine angle lesions: re-evaluating your diagnosis. (8th February 2013) - Walkden, Andrew; Shekhar, Himanshu; Fouyas, Ioannis; Gibson, Rod
Abstract : An unusual presentation of a life-threatening cerebellopontine abscess shows the importance of re-evaluating existing diagnoses when the clinical picture changes. Despite being rare, brain abscess is a potentially fatal condition that requires early radiological and surgical intervention. It has a varied presentation, with many cases showing no localising typical features, making it hard to diagnose at presentation. A high index of suspicion should be applied to cases exhibiting rapidly changing neurology. This is the first reported case of cerebellopontine abscess with no primary infective foci.